Cross Cultural Management Affect on Organizational Climate of ABC Inc - Pan LiangLiang; Suwatana Tungsawat (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2022)
In the process of economic globalization, transnational corporations are gradually rising and developing. However, multinational corporations form two different regional and cultural resources integration under the condition of various capital sources. Therefore, how to effectively carry out cross-cultural management in transnational corporations has an essential impact on the resource integration and benefit improvement of multinational corporations. This paper mainly takes the cross-cultural management of ABC company as the research object, defines the basic concepts of transnational corporations and cross-cultural management, and analyzes the importance of organizational climate and cross-cultural management in multinational corporations.